Effect of the expression of DRαEβ(NOD) molecule on the development of insulitis and diabetes in the non-obese diabetic (NOD) mouse - YAMANE, K (Blackwell Science Inc, 1996)
Previous studies have shown that a transgenic I-Eα gene, the mouse homologue of human DRα gene, prevents the development of insulitis and hence of diabetes in NOD mice. To investigate the mechanism of this prevention, we generated two strains of NOD mice expressing DRαEβ molecule: DRα-24-NOD expressing DRαEβ molecule on thymic epithelial cells (TEC) and bone marrow-derived cells (BDC), and DRα-30-NOD expressing DRαEβ molecule only on the TEC, and these mice were monitored for disease development. Because the DRαEβ molecule reconstituted I-E controlled immune regulation, it would become clear which cell type, TEC or BDC, was responsible for the I-E-mediated disease protection. To our surprise, however, DRα-24-NOD developed insulitis and diabetes comparably to non-transgenic littermates. This suggested that the difference in structure between DRα and Eα molecules contributed to the difference in preventive effect on the development of insulitis and diabetes between DRα-24-NOD and Eα-NOD. In an analysis of the T cell proliferative responses to glutamic acid decarboxylase (GAD) 65-derived peptides which were known to be diabetogenic autoantigens, it was shown that DRα-24-NOD and NOD acquired comparable level of T cell response to GAD 509–528 but 5–10-fold higher response was observed in Eα-NOD. This suggested that I-A(NOD) and EαEβ(NOD) molecules could present GAD 509–528 peptide to T cells, while DRαEβ(NOD) could not. Furthermore, T cells from DRα transgenic mice showed proliferative response to antigen-presenting cells from Eα transgenic mice in primary mixed lymphocyte reaction. This also suggested that the EαEβ molecule does differ in structure and peptide binding from the DRαEβ molecule. Present data suggested a possibility that the T cell repertoire selection, or the T cell response to GAD 65 and/or other unknown antigens specifically mediated by I-E molecule, may contribute to the prevention of disease development in Eα-NOD.